Comparison of pipeline embolization device and flow re-direction endoluminal device flow diverters for internal carotid artery aneurysms: a propensity score-matched cohort study - Griessenauer, Christoph J.; Thomas, Ajith; Möhlenbruch, Markus Alfred (Neurosurgery, 2019)
AbstractBACKGROUND. Flow diversion has become an accepted endovascular treatment modality for intracranial aneurysms. Studies comparing different types of flow
Published: 12 December 2018
Gesehen am 07.01.2020